2017
DOI: 10.1002/pits.22067
|View full text |Cite
|
Sign up to set email alerts
|

Latino immigrant parents’ financial stress, depression, and academic involvement predicting child academic success

Abstract: The current study examines Mexican-heritage immigrant parents' financial stress, English language fluency, and depressive symptoms as risk factors for parental academic involvement and child academic outcomes. Participants were 68 Latino immigrant (from Mexico) third and fourth graders and their parents. Results from a structural equation model analysis indicated that Latino parents who reported greater financial stress also reported higher levels of depressive symptoms; this, in turn, was related to lower par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 59 publications
2
12
0
2
Order By: Relevance
“…Our findings are consistent with the Family Stress Model, which posits that economic hardships, such as low income or high debt-to-asset ratio, increase economic pressures, which negatively affect family functioning and parent adjustment, and consequently, child development outcomes 23 25 , including language 27 29 . Although we did not directly measure financial strain, we hypothesize that in the current study, parents participating at days later in the month were more occupied with financial concerns, which affected the speech they used in interactions with their child.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with the Family Stress Model, which posits that economic hardships, such as low income or high debt-to-asset ratio, increase economic pressures, which negatively affect family functioning and parent adjustment, and consequently, child development outcomes 23 25 , including language 27 29 . Although we did not directly measure financial strain, we hypothesize that in the current study, parents participating at days later in the month were more occupied with financial concerns, which affected the speech they used in interactions with their child.…”
Section: Discussionsupporting
confidence: 88%
“…One possibility may be that other unmeasured aspects of parenting mediated the effect of maternal stress on English acquisition. For instance, one study of Latinx American families found that parents’ reduced involvement in their children’s education was associated with children’s academic underachievement (Gilbert et al, 2017). Thus, other parental factors may better account for associations between maternal perceived stress and child English acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, young refugees in Australia experience stress from language issues, a lack of career opportunities and difficulties in seeking further education, but are more likely to be able to cope with these stressors with social support from family, friends and their ethnic community (Joyce & Liamputtong, 2017). According to a study on Latino immigrants, parents' financial stress affects not only their mental health but also their children's' academic performance (Gilbert et al, 2017); however, since this study did not include parental stress or children under age 18, the association between the result and parental responsibilities is not clear. Future studies should include parenting stress and children under age 18 who may be affected by parents' stress.…”
Section: Discussionmentioning
confidence: 99%